Development of B D F-AR 2 (Physics Digital Book Based Augmented Reality) to train students' scientific literacy on Global Warming Material - Abd. Kholiq (Universitas Lambung Mangkurat, 2020)
There have been many developments in digital books, but they are different from BDF-AR2 (Physics Digital Book Based Augmented Reality), this is because the developed BDF-AR2 has features that can train the literacy skills of learners including Augmented Reality (AR) feature so that learning can be more real. The main objective of this research is to describe eligibility (validity, practicality, and effectiveness) of BDF-AR2 media that has been developed This research employed Hannafin & Peck Model development design using by using instruments of media validation, learning completion and validated test instrument. Media validation was carried out by three media experts and resulted in the media B D F-AR 2 (Physics Digital Book Based Augmented Reality) on the global warming material is classified as very valid (93.5%). As for practicality (use BDF-AR2 media in learning) is obtained 83.29% and categorized very good. While for effectiveness (students' scientific literacy skills), it was found that students' scientific literacy skills for 36.67% of students are in a good category, 56.67% of student have an average level and 6.96% of students had poor category for literacy competence science in explaining the phenomenon. As for scientific literacy competencies in interpreting data and evidence scientifically, 30% students have good grades, 66.67% had a fair grade and 3.33 had a poor grade. Referring to the results of validity, practicality, and effectiveness of use BDF-AR2 in learning, it can be concluded that the developed BDF-AR2 is feasible to use in learning. The implication of this research is to present a media that supports 21st-century learning that has been proclaimed by the government.